GENOTYPING AND ANALYSIS OF rs27037 POLYMORPHISM FOR ANKYLOSING SPONDYLITIS - Akbulut, Ekrem; Erdemir, Aysegul; Ozgen, Metin; Baskin, Yasemin; Yalcin, Femin; Balik, Dilek Turgut (YILDIZ TECHNICAL UNIV, 2015)
Ankylosing spondylitis (AS) is a systemic, chronic and inflammatory disease in which the spine and peripheral joints are sore and which causes restriction of movement particularly in axial joints. Many genetic, environmental and immunological factors have roles in the development of the disease. Prevalence of AS which causes work force loss and decrease in life quality is %0,15 - 0,49. Single nucleotide polymorphisms (SNP) are single base changes frequently observed in human genome and they are important molecular indicators used for disease susceptibility, development of disease, medicine response and disease diagnosis. In studies carried out with different populations, disease risk and some SNPs are associated. Research on these SNPs, the effects of which haven't evaluated in our population yet, will make contributions to early diagnosis of the disease before the spine deformation occurs. In this study, genotyping and analyzing of rs27037 polymorphism associated with AS in various populations were carried out in order to determine the genetic risk susceptibility in our society. The study was conducted with 100 AS patients and 101 controls subject, the iPLEX (R) method was used for the genotyping of rs27037. With this study, it was demonstrated that in our population there was no risk association between AS and rs27037 polymorphism. In the study, while the OR value of T allele was determined to be 1,06 (%95 Cl = 0,69 - 1,65), rs27037 wasn't associated with disease risk in our population as p value was found to be 0,776.
Keywords: Ankylosing spondylitis (AS); single nucleotide polymorphism (SNP); SNP genotyping; Engineering